2019
DOI: 10.1364/oe.27.018601
|View full text |Cite
|
Sign up to set email alerts
|

Quantum noise limited nanoparticle detection with exposed-core fiber

Abstract: Label-free biosensors are important tools for clinical diagnostics and for studying biology at the single molecule level. The development of optical label-free sensors has allowed extreme sensitivity, but can expose the biological sample to photodamage. Moreover, the fragility and complexity of these sensors can be prohibitive to applications. To overcome these problems, we develop a quantum noise limited exposed-core fiber sensor providing robust platform for label-free biosensing with a natural path toward m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Crucially, both experiments [155,319] demonstrate that noise in the system follows a linear scaling with local oscillator power, consistent with quantum-limited noise (Figure 15c). Therefore, these sensors operate at the fundamental limit for a coherent light probe, i.e.…”
Section: Quantum-limited Single Molecule Sensorssupporting
confidence: 63%
See 1 more Smart Citation
“…Crucially, both experiments [155,319] demonstrate that noise in the system follows a linear scaling with local oscillator power, consistent with quantum-limited noise (Figure 15c). Therefore, these sensors operate at the fundamental limit for a coherent light probe, i.e.…”
Section: Quantum-limited Single Molecule Sensorssupporting
confidence: 63%
“…The high sensitivity detection was achieved by a heterodyne measurement, balanced at the detector by the pure local oscillator. This measurement scheme was recently developed to use an exposed core fibre sensor [319]. These sensors are more robust (around 120 μm diameter; compared with 500 nm tapered fibres) and can be produced with much longer sensing regions than the <1 mm provided by the previous setup.…”
Section: Quantum-limited Single Molecule Sensorsmentioning
confidence: 99%
“…Nevertheless, several techniques have been developed that are able to resolve macromolecules with sizes down to a few nanometers, far below the scale of the optical wavelength. Figure 1 illustrates a number of these techniques, including optical cavity or plasmonic resonance enhanced sensors 8 13 , dark-field heterodyne microscopy 4 , 14 16 , interferometric scattering microscopy 6 , 17 – 19 , and plasmonic optical traps 20 22 .…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, we have investigated weak-force sensing in a squeezed cavity and theoretically showed that (i) the SQL cannot be surpassed in the case of G = 0 or θ = 0, (ii) the measurement precision of weak-force detection can be remarkably improved at the coupling strength smaller than g SQL by tuning the parametric phase and gain, and (iii) under the approximation of κ ω, quantum noise can be reduced without losing mechanical-mode information. Our work provides new insight in strengthening the sensitivity of a force sensor with the assistance of intracavity squeezing, which can be also extended into other systems of quantum sensing with e.g., waveguide [84,87], interferometer [88], or parity-time (PT ) symmetric microcavity [89][90][91]. In the future, we plan to extend our work to study the weakforce measurement with the help of two-mode squeezing or quantum entanglement [92][93][94], squeezed mechanical modes [70,95], or squeezed sources in hybrid COM devices [96,97].…”
Section: Discussionmentioning
confidence: 94%